2018
DOI: 10.1016/j.chemosphere.2018.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Environmental occurrence and hazard of organic UV stabilizers and UV filters in the sediment of European North and Baltic Seas

Abstract: UV absorbing compounds are of emerging concern due to their large production volumes, their persistence or pseudo-persistence, and their potential adverse effects. This is the first study investigating the environmental occurrence and potential hazard of organic UV stabilizers and UV filters in the North and Baltic Sea surface sediments, including the connecting Skagerrak and Kattegat straits. In total, nineteen substances were identified over the entire study area, including the rarely studied compounds ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Recently, the environmental impact related to the excessive consumption of these emerging pollutants is being a matter of concern. Several research works have confirmed the widespread presence of organic UV filters in aquatic ecosystems, such as urban underground water, river, lakes, and the sea [3][4][5][6][7], coming from recreational activities as well as the inefficiency of wastewater treatments plants to eliminate them. Moreover, relevant concentration levels of several chemical sunscreens were detected in aquatic biota, like fish, mussels and marine mammals [8][9][10], evidencing a marked tendency to accumulate in living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the environmental impact related to the excessive consumption of these emerging pollutants is being a matter of concern. Several research works have confirmed the widespread presence of organic UV filters in aquatic ecosystems, such as urban underground water, river, lakes, and the sea [3][4][5][6][7], coming from recreational activities as well as the inefficiency of wastewater treatments plants to eliminate them. Moreover, relevant concentration levels of several chemical sunscreens were detected in aquatic biota, like fish, mussels and marine mammals [8][9][10], evidencing a marked tendency to accumulate in living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these compounds has increased in recent decades to protect against sunlight. Depending on their purpose, these compounds can be added to different consumer goods such as plastics, paints, and textiles to protect polymers and pigments against photodegradation and to prevent discolouring, or they can be used in personal care products (PCPs) to protect human skin and hair against sun damage, such as lotions, creams, and fragrances [2,3]. The input pathway of these compounds to the marine environment can be direct due to recreational activities, such as swimming or aquatic sports, but the main source is indirect, arriving through the sewage effluents from wastewater treatment plants, since the current treatment cannot completely degrade certain compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A different stand was adopted in the case of sewage sludge. Scarce information on concentration levels and EHMC behaviour in sewage sludge prompted the Commission (EU) to take action to check whether Member States can monitor the presence of EHMC in a sediment in a credible and comparable manner (Apel et al 2018). Therefore, monitoring of sewage sludge in this area was intensified.…”
Section: Introductionmentioning
confidence: 99%